Drosophila XBP1 Expression Reporter Marks Cells under Endoplasmic Reticulum Stress and with High Protein Secretory Load. - Ryoo, H.D.; Li, J.; Kang, M.J. (PLoS ONE, 2013)
Expression of genes in the endoplasmic reticulum (ER) beyond its protein folding capacity activates signaling pathways that are collectively referred to as the Unfolded Protein Response (UPR). A major branch of the UPR pathway is mediated by IRE1, an ER-tethered endonuclease. Upon ER stress-induced activation, IRE1 splices the mRNA of XBP1, thereby generating an active isoform of this transcription factor. During normal Drosophila development, tissues with high protein secretory load show signs of IRE1/XBP1 activity indicative of inherent ER stress associated with those cell types. Here, we report that the XBP1 promoter activity itself is enhanced in secretory tissues of Drosophila, and it can be induced by excessive ER stress. Specifically, we developed a Drosophila XBP1 transcription reporter by placing dsRed under the control of the XBP1 intergenic sequence. DsRed expression in these xbp1p>dsRed transgenic flies showed patterns similar to that of xbp1 transcript distribution. In healthy developing flies, the reporter expression was highest in salivary glands and the intestine. In the adult, the male reproductive organs showed high levels of dsRed. These tissues are known to have high protein secretory load. Consistently, the xbp1p>dsRed reporter was induced by excessive ER stress caused by mutant Rhodopsin-1 overexpression. These results suggest that secretory cells suffer from inherent ER stress, and the xbp1p>dsRed flies provide a useful tool in studying the function and homeostasis of those cells.